2021
DOI: 10.1038/s41598-021-98583-8
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a striped catfish skin explant model for studying the skin response in Aeromonas hydrophila infections

Abstract: Teleost fish skin serves as the first line of defense against pathogens. The interaction between pathogen and host skin determines the infection outcome. However, the mechanism(s) that modulate infection remain largely unknown. A proper tissue culture model that is easier to handle but can quantitatively and qualitatively monitor infection progress may shed some lights. Here, we use striped catfish (Pangasius hypophthalmus) to establish an ex vivo skin explant tissue culture model to explore host pathogen inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Since fish skin mucus plays a critical role in stimulating and regulating the immune response, we hypothesized that AH-challenged skin mucus could induce the observed skin immune response. To test this hypothesis, an ex vivo skin model ( 28 ) was used to create an interactive environment between the skin and the mucus ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since fish skin mucus plays a critical role in stimulating and regulating the immune response, we hypothesized that AH-challenged skin mucus could induce the observed skin immune response. To test this hypothesis, an ex vivo skin model ( 28 ) was used to create an interactive environment between the skin and the mucus ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…3E ). Our previous study showed a significant immunostimulatory effect when inoculating the same amount of AH directly onto the skin model without mucus ( 28 ). Therefore, striped catfish skin mucus has a protective role in response to AH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some ulcerative lesions caused by only bacteria have been observed in UM epidermis ( Noga et al, 1991 ). Skin ulceration and muscular necrosis are dominated by A. hydrophila , the freshwater pathogen would cause infection-related mortality in catfish farming systems ( Siao et al, 2021 ). Infections caused the loss of 3 million pounds of farm-raised catfish in Alabama, United States, in 2017, making A. hydrophila the most prevalent pathogen in catfish ( Siao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Skin ulceration and muscular necrosis are dominated by A. hydrophila , the freshwater pathogen would cause infection-related mortality in catfish farming systems ( Siao et al, 2021 ). Infections caused the loss of 3 million pounds of farm-raised catfish in Alabama, United States, in 2017, making A. hydrophila the most prevalent pathogen in catfish ( Siao et al, 2021 ). However, within the same species of fish, they found different mucosal microbiomes ( Butt and Volkoff, 2019 ).…”
Section: Introductionmentioning
confidence: 99%